Whistle-blowing as an aspect of amar ma’aruf nahi munkar in institutional governance - Khalid, Haniza; Abd Samad, Khairunnisa; Kayadibi, Saim (2015)

(untitled)
A key challenge in preventing and fighting corruption is to detect and expose bribery, fraud, theft of public funds and other acts of wrongdoing. One of the most direct methods of exposing corruption in corporate or public institutions is whistleblowing. Many countries have introduced whistleblowing provisions to help deter corrupt behaviour and guide formal investigations into them. However, Muslim countries still lag far behind in this respect, perhaps out of structural inertia as well as the false belief that public disapprobation is not the way Muslims deal with one another. We argue that within reasonable limits whistleblowing is perfectly ingrained in Islam’s ‘‘amr bi-l-ma’ruf wa-nahy ‘an al-munkar” i.e., ‘enjoining good and forbidding wrong’ principle of social behaviour and is an important contributor to the society’s overall Maqasid al-Shariah. It is also interesting that while many academic studies have established the link between cultural and ethical values and whistle-blowing motivations, very few specifically study whistle-blowing within the Islamic moral philosophy framework. This paper attempts to fill this void by drawing from important Muslim writings why whistleblowing should not be downplayed and suggests several codes of conducts principles which can be useful in guiding the crafting of whistleblowing systems. An implication for modern-day managers is that by leveraging on member’s feelings of God-consciousness as well as awareness of whistleblowing obligations in religion, an organization’s internal control can be greatly strengthened.